A technical feasibility study of a piezoelectric energy harvesting system applied to sports shoe insoles - Norabuena Aliaga, Fiama Vanessa (2021)
This research proposes the development of an energy harvesting system applied to sports shoe insoles, which uses human footsteps for energy generation. The concepts of energy harvesting and the phenomenon of piezoelectricity were used to manufacture a prototype consisting of a system with eleven piezoelectric sensors and a 3D printed insole made from PLA material. The prototype was tested using simulated footsteps, thus generating up to 1 V when an LED diode turned on. However, the energy generated was not enough to charge a low-power storage unit.